ASSESSMENT OF INVESTING ACTIVITY OF FARMERS USING THE EU FUNDS ON THE EXAMPLE OF LUBELSKIE VOIVODESHIP - Lorencowicz, Edmund; Cupiał, Michał (Acta Scientiarum Polonorum. Oeconomia, 2013)
The paper presents the use of EU funds by farmers on the territory of Lubelskie Voivodeship used for investment activities concerning agricultural technology. Analysis covered pre-accession funds and activities within PROW (the Rural Areas Development Programme). From 2004 to the middle of 2011, 15,410 beneficiaries used over PLN 1.5 mid. Owners of bigger farms of the average area over 40 ha were beneficiaries. The average value of the investment was PLN 238 thousand and was increasing along with the farm area. Average age of beneficiaries was 38 years.